Предмет: Алгебра, автор: park26690

решите плиз до завтра 20:00​

Приложения:

Ответы

Автор ответа: zzyaba
1

Ответ:

Объяснение:

1) через теорему Виета:

х1+х2=6

х1*х2=-27, выходит, что х1= -3, х2=9

2) через теорему Виета:

х1+х2=9

х1*х2=20, получаем х1=4, х2=5.

3) 3x^{2} - 12х + 2х -8 = 5

3x^{2} - 10х - 8 = 5

3x^{2} - 10х -8 -5 = 0

3x^{2} + 3х - 13 х - 13 = 0

3х(х+1)-13(х-1)=0

(х+1)(3х-13)=0

х= -1

х= 13/3

5)  х1+х2= -8

х1*х2=-263

6) х1+х2=14

х1*х2=5

7) х1+х2= -12/5

х1*х2= -7/5

Похожие вопросы